Christian Epistemology in Theological Education: Integration of Revelation, Rationality, and Theological Formation in the Global Era - Herbin Simanjuntak; Yohanes Nduru; Mawarni Waruwu (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This article examines Christian epistemology in the context of theological education by highlighting the integration of divine revelation, human rationality, and theological formation processes in a global era characterized by pluralism, digitalization, and a crisis of truth authority. The main problem raised is the epistemological fragmentation in modern theological education that tends to separate revelation from rationality, thus impacting the weakness of faith formation and theological integrity. This study aims to formulate an integrative model of Christian epistemology that can address these challenges. The method used is a qualitative approach with a systematic literature study of classical and contemporary theological sources, as well as a conceptual analysis of Christian epistemological paradigms. The results show that the integration of revelation, reason, and faith experience produces a holistic epistemological model that not only strengthens theological foundations but also shapes students' spiritual character in a transformative manner. The main synthesis of this study is the Epistemological Theological Integration Framework (ETIF) model, which emphasizes that theological truth must be understood as a unity between biblical authority, rational reflection, and the practice of faith. In conclusion, an integrated Christian epistemology can serve as a solid foundation for theological education in facing global challenges and shaping a generation of contextual, reflective, and spiritual theologians.